Analisis Tindak Tutur Lokusi pada Video Kuliah Bisnis dalam Kanal YouTube Kuliah Kehidupan - Riri Citra Melisa; Anton April Laksono; Ulya Fadhilatur Rohmah; Adhitya Indra Pratama Putra; Sekar Cahya Ningrum; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Uki Hares Yulianti (STIKes Ibnu Sina Ajibarang, 2025)
Illocutionary acts are a type of speech act that functions to convey information to the interlocutor and can also be used to perform an action. This research uses a qualitative descriptive method, which utilizes qualitative data and is presented descriptively. This method was chosen because it aligns with the characteristics of qualitative research that emphasizes description without statistical analysis. Qualitative research is a type of research where the results cannot be obtained through statistical procedures or other measurements. This research uses a qualitative descriptive method, which utilizes qualitative data and is presented descriptively. In writing this article, methodological and theoretical approaches are used. The methodological approach applied is qualitative descriptive, while the theoretical approach used is the pragmatic approach. Based on the data analysis results from the Business Lecture video on the YouTube channel Kuliah Kehidupan, locutionary acts in the form of questions, news, information, and commands were found. The benefit of this research is to expand understanding and knowledge about locutionary acts.